Ceramic compacts as human hard tissue implants: their microstructure and wear strength. (20th January 2011) - Hasan, Zahir
Besides a number of applications, ceramic materials are also used as an alternative to human tissues because of their good wear resisting properties and high strength. High-purity aluminium oxide is potentially an attractive implant material for total synovial joint replacement, and other body implants due to its bioinertity. In the present study, an attempt has been made to study the mechanical properties of sintered alumina, calcined alumina (99%) and alumina zircon which are used as implants in human hard tissues. The powders were compacted at six level of compaction load and sintered at 1, 550°C for two hours. Mechanical properties and wear volume of the compacts were studied. Scanning electron microscope (SEM) of the compacts after wear was also studied. Compaction load enhanced density and crushing strength while wear volume decreased with an increase in compaction load. Alumina zircon exhibited minimum wear volume and calcined alumina showed maximum wear volume.